2004
DOI: 10.1002/jcc.20121
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on reaction mechanism of the fluoromethylene radical with nitrogen dioxide

Abstract: The complex doublet potential energy surface for the reaction of 1CHF with NO2, including 14 minimum isomers and 30 transition states, is explored theoretically at the B3LYP/6-311G(d,p) and CCSD(T)/6-311G(d,p) (single-point) levels of theory. The initial association between 1CHF and NO2 is found to be the carbon-to-middle-nitrogen attack forming an energy-rich adduct a (HFCNO2) with no barrier, followed by concerted O-shift and C--N bond rupture leading to product P2 (NO + HFCO), which is the most abundant. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Fitting the column density of the nitroformyl radical with pseudo-first order kinetics as we have done with eqn (2), and assuming the primary formation pathway to OCNO is shown in eqn (3), this means that the time it takes to dissociate a nitrogen molecule producing two nitrogen atoms is negligible with respect to the speed of reaction of the nitrogen atom shown in eqn (3). According to the column density profile in Fig.…”
Section: Kinetics and Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fitting the column density of the nitroformyl radical with pseudo-first order kinetics as we have done with eqn (2), and assuming the primary formation pathway to OCNO is shown in eqn (3), this means that the time it takes to dissociate a nitrogen molecule producing two nitrogen atoms is negligible with respect to the speed of reaction of the nitrogen atom shown in eqn (3). According to the column density profile in Fig.…”
Section: Kinetics and Dynamicsmentioning
confidence: 99%
“…The two nitrogen atoms will be mostly produced in the excited electronic state ( 2 D) and in the ground electronic state ( 4 S), the exact ratio being largely dependent on the amount of energy absorbed by the nitrogen molecule. 8,9 These nitrogen atoms can then react with a carbon dioxide molecule as shown in eqn (3). In comparison, this reaction was also studied in the gas phase where the internally excited OCNO intermediate could not be stabilized via phonon coupling; the reaction complex was found to immediately dissociate to CO þ NO.…”
Section: Kinetics and Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was followed by the same group with the chloride and fluoride substituted carbenes. 7,8 It was reported that carbenes react with NO 2 without any activation energy barrier. The most stable end products of these reactions are aldehyde derivatives and NO.…”
Section: Introductionmentioning
confidence: 99%
“…The sequestering of greenhouse gases like SO x , NO x , CO x , etc., is one of the biggest challenges of modern-day chemical research because they not only cause environmental pollution but also enhance fatal health problems. Thus, nabbing these hazard gases at their respective sources and metamorphosing them into valued chemicals is the prime research focus of several groups around the globe. Various chemical technologies have been developed thus far in this regard. Among them, covalent organic framework (COF), metal organic framework (MOF), ionic liquid, metal alkyl and aryl complexes, electron rich amines, etc., are the frontrunners to be the best candidates for this purpose.…”
Section: Introductionmentioning
confidence: 99%